Fabrication of micro/nanowire fibres, novel fibre devices and their applications - Cui, Long (2016)
The research topic comprises of the fabrication of specialty fibres, fibre-based novel devices and their applications. The focus of fabrication is to realize novel high-throughput micro and nanostructured fibres through scalable methods, the newly developed planar-fibre nanomanufacturing, which combines the conventional microstructuring techniques with fibre drawing. This hybrid process enables fabrication of high aspect ratio (length-to-width ratio) one- dimensional (1D) nanostructures, such as metallic micro/nanowires and nanoribbon- like chalcogenide semiconductors (e.g. germanium-antimony-telluride, GeSbTe or simply GST) embedded in a glass-clad material of choice. Based on some fibre-based device designs, functional fibre-based photodetectors are achieved by multilayer coatings and electrode fabrication. The conventional deposition methods behind fibre coating, thermal or electron-beam evaporation and RF sputtering technique, are employed to carry out the desired device fabrication. As far as applications, we will target fiberized photodetectors, photodiodes, plasmonics and non-linear optics.